2014
DOI: 10.1246/bcsj.20140247
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hydrophilic and Hydrophobic Carbon Nanoparticles from Benzene/Water Bilayer Solution with Femtosecond Laser Generated Plasma Filaments in Water

Abstract: We synthesized hydrophilic and hydrophobic carbon nanoparticles (CNPs) by femtosecond laser (0.8¯m, 40 fs) irradiation of the water layer of an aerated benzene/water (B/W) bilayer solution. Focusing intense femtosecond laser pulses onto water creates a high density of reactive species such as hydroxyl radicals in a well-confined volume; i.e., plasma filament. The properties of the particle surface were controlled simply by adjusting the laser focusing position, the duration between the preparation of B/W bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…In addition, our procedurew orks at room temperature, at aqueous, and aeratedconditions without any harsh reagents. [17] We concluded that the productiono f dense CNPs in B/W bilayer solution was due to the continuous supply of benzene into water layer through the B/W interface. Those particles did not show hydrophilicity at all:t he particles did not move to the water layer (upper layer,F igure 1d)b ut stayed in the HFB layer (lower layer) after the addition of water followed by shaking.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…In addition, our procedurew orks at room temperature, at aqueous, and aeratedconditions without any harsh reagents. [17] We concluded that the productiono f dense CNPs in B/W bilayer solution was due to the continuous supply of benzene into water layer through the B/W interface. Those particles did not show hydrophilicity at all:t he particles did not move to the water layer (upper layer,F igure 1d)b ut stayed in the HFB layer (lower layer) after the addition of water followed by shaking.…”
mentioning
confidence: 82%
“…The atomic composition of fluorine in the CNPs as wella so nt heir surface was highert han in previously reported methods. [17] In addition, the yield of CNPs were enhanced by using benzene/water (B/W) bilayer solution. The HFB turned dark yellow upon femtosecond laser irradiation and was accompanied by black particles (Figure 1a).…”
mentioning
confidence: 99%
See 3 more Smart Citations